DIMENSI TEORITIS DAN PRAKTIS DALAM KEPEMIMPINAN PROFETIK - Aminah, Neneng; Nurhayati, Neng; Patimah, Siti; Lugowi, Rifyal Ahmad (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This research aims to analyze how prophetic leadership integrates moral, spiritual, and ethical values of Islam into modern management practices to create just and sustainable leadership.Method: The approach used is literature study, examining the teachings of the Qur'an, Hadith, and various case studies of the implementation of prophetic leadership in educational institutions and the business world. The analysis is conducted qualitatively to understand the application of Islamic values in the context of contemporary leadership.Results: Findings show that values such as trustworthiness, justice, transparency, and integrity are fundamental in building organizations that are not only efficient but also ethical and sustainable. Prophetic leadership can create a humanistic work culture and enhance organizational loyalty and performance.Novelty: This research presents innovation by combining traditional Islamic principles with the needs of modern leadership, resulting in a holistic and adaptive leadership paradigm. The main contribution lies in the development of management and leadership literature that emphasizes spiritual values as a key pillar in strategic decision-making.